Life Course of Physical Activity and Risk and Prognosis of Amyotrophic Lateral Sclerosis in a German ALS Registry. (9th November 2021) - Rosenbohm, Angela; Peter, Raphael; Dorst, Johannes; Kassubek, Jan; Rothenbacher, Dietrich; Nagel, Gabriele; Ludolph, Albert C.; Andres, Frank; Arnold, Guy; Baier, Hartmut; Baezner, Hansjoerg; Beattie, James; et al.
Abstract : Background and Objectives: Whether physical activity (PA) is a risk factor for amyotrophic lateral sclerosis (ALS) is controversial because data on lifelong PA are rare. The main objective of this study is to provide insight into PA as a potential risk factor for ALS, reporting data on cumulative PA, leisure-time PA, and occupational PA. This study also aims to gather evidence on the role of PA as a prognostic factor in disease course. Methods: Lifetime PA values collected by questionnaires addressing work and leisure time were quantified into metabolic equivalents (METs). A population-based case-control study embedded in the ALS Registry Swabia served to calculate the odds ratio (OR) of ALS by PA in different time intervals and prognosis. Results: In ALS cases (393 cases, 791 age- and sex-matched controls), we observed reduced total PA at interview and up to 5 years before interview compared to controls. Total PA was not associated with ALS risk 5 to 55 years before interview. Heavy occupational work intensity was associated with increased ALS risk (OR 1.97, 95% confidence interval 1.34, 2.89). Total PA levels were associated with survival in a nonlinear manner: inactive patients and highest activity levels (25 MET-h/wk) revealed the worst survival time of 15.4 and 19.3 months, respectively. Best median survival with 29.8 months was seen at 10.5 MET-h/wk after adjustment for other prognostic factors. Discussion: Lifetime combined PA decreased sharply several years before disease onset compared to controls. The risk of developing ALS was not associated with former total PA levels 5 to 55 years before interview in contrast to occupational PA, probably reflecting work-associated exposures. We found a strong nonlinear association of current and prediagnostic PA level and survival in ALS cases with the best survival with moderate PA. PA intensity may be a disease-modifying factor with an unfavorable outcome in sedentary and hyperactive behavior. Classification of Evidence: This study provides Class III evidence that PA was not associated with the development of ALS.